Standardized training for AVT pacing in paediatric patients with postoperative junctional ectopic tachycardia. Issue 4 (6th March 2018) - Entenmann, Andreas; Dittrich, Susann; Hessling, Vera; Niederwanger, Christian; Cortina, Gerard; Michel, Miriam
ABSTRACT: Background: Junctional ectopic tachycardia is a serious complication of surgery for paediatric congenital heart disease. R‐wave synchronized atrial (AVT) pacing, an innovative temporary pacing technique, restores atrioventricular synchrony in these patients. The method is highly effective but technically complex. A standardized training model exists for doctors but not for paediatric intensive care nurses. Aims: This study seeks to evaluate whether a standardized programme involving simulation and vignettes increases knowledge of AVT pacing and accuracy of its documentation, as well as recognition and management of specific complications. Study design: This study was an experimental simulation test with before and after descriptive evaluation. Methods: A custom‐made simulation model was used in combination with standardized training. Before and after training, 10 paediatric nurse specialists were asked to document pacing, to identify complications and to intervene as necessary. Four clinical scenarios were presented: effective AVT pacing, ineffective AVT pacing, pacing with narrow interval between atrial pacing and ventricular sensing and pacemaker‐induced tachycardia. Identification and management of complications were evaluated using a 3‐point scale. Results: Training improved the quality of documentation and complication management. At outset, documentation by 1 of 10 participants was completely correct, and after training, documentation by 8 of 10 participants was completely correct. Before training, 30% of interpretations of the four presented clinical scenarios were correct (12/40) versus 83% (33/40) after training. The decision to notify a doctor of a complication was correct in 83% (33/40) before versus 95% (38/40) after the training. Conclusion: Standardized simulation training improves quality and safety in AVT pacing, with more accurate documentation of the pacing mode and better recognition and management of specific complications during pacing. Relevance to clinical practice: AVT pacing should be performed in conjunction with standardized simulation training in paediatric cardiac intensive care units.